Negative electrode for lithium secondary battery and lithium secondary battery including the same

By adopting a pattern coating structure of organometallic material in the negative electrode of lithium-ion secondary battery, the problems of insufficient negative electrode life and resistance are solved, and better battery performance is achieved.

JP2025040939APending Publication Date: 2025-03-25SAMSUNG SDI CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024120793
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-12
Filing Date
2024-07-26
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The negative electrodes of existing lithium-ion secondary batteries have shortcomings in terms of life and resistance, which affect the overall performance of the battery.

Method used

Using a negative electrode with a mode coating structure of an organometallic material, an adhesive force between the electrodes is improved and conductivity is maintained by forming a coating with an organometallic material between the current collector and the negative electrode active material layer.

Benefits of technology

It realizes the excellent life characteristics and low resistance of the negative electrode, and improves the overall performance of the lithium-ion secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025040939000001_ABST
    Figure 2025040939000001_ABST
Patent Text Reader

Abstract

To provide a negative electrode for a lithium secondary battery and a lithium secondary battery including the same.SOLUTION: The present invention relates to a negative electrode for a lithium secondary battery and a lithium secondary battery including the same, and the negative electrode includes a current collector, a negative electrode active material layer including a negative electrode active material, and a coating layer positioned between the current collector and the negative electrode active material layer, including an organometallic material, and having a pattern shape.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a negative electrode for a lithium secondary battery and a lithium secondary battery including the same. [Background technology]

[0002] In recent years, with the rapid spread of electronic devices that use batteries, such as mobile phones, notebook computers, and electric vehicles, the demand for lithium secondary batteries that are small, lightweight, and have relatively high capacity is rapidly increasing. Accordingly, research and development to improve the performance of lithium secondary batteries is being actively conducted.

[0003] A lithium secondary battery is a battery that includes a positive electrode and a negative electrode, each of which includes an active material capable of intercalating and deintercalating lithium ions, and an electrolyte. When lithium ions are intercalated into and deintercalated from the positive electrode and the negative electrode, oxidation and reduction reactions occur, producing electrical energy. Summary of the Invention [Problem to be solved by the invention]

[0004] One embodiment is to provide a negative electrode for a lithium secondary battery that exhibits excellent life characteristics and low resistance.

[0005] Another embodiment provides a lithium secondary battery including the negative electrode. [Means for solving the problem]

[0006] One embodiment provides a negative electrode for a lithium secondary battery, comprising: a current collector; a negative electrode active material layer including a negative electrode active material; and a coating layer located between the current collector and the negative electrode active material layer, the coating layer including an organometallic material, and having a patterned shape.

[0007] According to another embodiment, there is provided a lithium secondary battery comprising: the negative electrode; a positive electrode; and an electrolyte.

[0008] The negative electrode for a lithium secondary battery according to an embodiment can exhibit excellent life characteristics and low resistance. [Brief description of the drawings]

[0009] [Figure 1] 1 is a cross-sectional view illustrating a negative electrode for a lithium secondary battery according to an embodiment of the present invention; [Diagram 2] 1 is a cross-sectional view illustrating a lithium secondary battery according to an embodiment of the present invention; [Diagram 3] 1 is a cross-sectional view illustrating a lithium secondary battery according to an embodiment of the present invention; [Figure 4] 1 is a cross-sectional view illustrating a lithium secondary battery according to an embodiment of the present invention; [Diagram 5] 1 is a cross-sectional view illustrating a lithium secondary battery according to an embodiment of the present invention; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, the present invention will be described in detail with reference to examples, which are presented by way of example only and are not intended to limit the present invention, which is defined only by the scope of the claims set forth below.

[0011] Unless otherwise specified in this specification, when a layer, film, region, plate, or other part is referred to as being "on" another part, this includes not only when it is "directly on" the other part, but also when there is another part in between.

[0012] Unless otherwise specified herein, the singular can also include the plural, and unless otherwise specified, "A or B" can mean "including A, including B, or including A and B."

[0013] As used herein, "combinations thereof" can mean mixtures, laminates, composites, copolymers, alloys, blends, reaction products, and the like of compositions.

[0014] Unless otherwise defined in this specification, the particle size may be the average particle size. Also, the particle size means the average particle size (D50) which means the diameter of the particles with a cumulative volume of 50% by volume in the particle size distribution. The average particle size (D50) can be measured by a method widely known to those skilled in the art, for example, by measuring with a particle size analyzer, or by measuring with a transmission electron microscope or a scanning electron microscope. As another method, the average particle size (D50) value can be obtained by measuring with a measuring device using dynamic light-scattering, analyzing the data, counting the number of particles for each particle size range, and then calculating from the data. Alternatively, the average particle size (D50) value can be obtained by measuring with a laser diffraction method. More specifically, when measuring by the laser diffraction method, the particles to be measured are dispersed in a dispersion medium, then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000) and irradiated with ultrasonic waves of about 28 kHz at an output of 60 W, and the average particle size (D50) based on the 50% standard of the particle size distribution in the measuring device can be calculated.

[0015] According to an embodiment, a negative electrode for a lithium secondary battery includes a current collector; a negative electrode active material layer including a negative electrode active material; and a coating layer having a pattern shape, the coating layer including an organometallic material and disposed between the current collector and the negative electrode active material layer.

[0016] In one embodiment, the negative electrode may have an organometallic material disposed in a pattern between the current collector and the negative electrode active material layer, thereby increasing adhesion between the current collector and the active material layer. In one embodiment, the coating layer having a pattern shape means that the coating layer does not completely cover the entire surface of the current collector, but is formed in some pattern, which means that the coating layer has a coated portion and an uncoated portion.

[0017] For example, the pattern shape may be a mesh shape, a dot shape, a diagonal line shape, an ellipse shape, a polygon shape, a diamond shape, a line shape, a wave shape, a triangular pyramid shape, or a combination thereof.

[0018] In one embodiment, the presence of a coating layer having a patterned shape in the negative electrode can be determined by computer tomography analysis or by disassembling a battery to obtain the negative electrode, removing the current collector, and analyzing the components of each part.

[0019] FIG. 1 is a cross-sectional view of an anode according to one embodiment, showing an anode 1 including a current collector 3, a coating layer 5 and an anode active material layer .

[0020] In the negative electrode according to one embodiment, the area of ​​the coating layer may be 10% to 50%, 15% to 50%, or 20% to 50% of the negative electrode active material layer area (100%). The area of ​​the coating layer means the ratio of the area (b) of the coating portion to 100% of the cross-sectional area of ​​the active material application region (a) shown in Fig. 1. For example, it means the percentage of the area occupied by the coating layer in contact with the active material layer to 100% of the active material layer area.

[0021] Since the coating layer has a pattern shape, for example, there are coated and uncoated parts, the coating part can provide adhesion between the current collector and the active material layer, and the uncoated part can maintain electrical conductivity since the current collector and the active material layer are in direct contact with each other. When the coating layer is included in the negative electrode at the above area %, it is appropriate because it can further increase the adhesiveness and the effect of maintaining electrical conductivity. If the coating layer is present in such a way that it completely covers the negative electrode active material layer, for example, 100% of the total area of ​​the negative electrode active material layer, the electrical conductivity is too low and it is not appropriate.

[0022] In an embodiment, the spacing between adjacent patterns may be 20 μm or more, 20 μm to 100 μm, or 20 μm to 80 μm. The spacing between patterns may refer to the spacing between one pattern and another adjacent pattern, as shown in FIG 1. When the spacing between patterns satisfies the above range, better electrical conductivity may be exhibited without increasing the contact resistance between the current collector and the active material layer.

[0023] The width of the pattern may be 5 μm to 30 μm, 5 μm to 25 μm, or 5 μm to 20 μm. The width of the pattern may be the width of one pattern as shown in Fig. 1. When the width of the pattern satisfies the above range, high adhesive strength can be obtained due to effective contact between the coating layer and the active material layer.

[0024] The thickness of the coating layer can be appropriately adjusted and is not necessarily limited.

[0025] In one embodiment, the organometallic material may be an organometallic compound in which a central metal ion is coordinated with an organic ligand, or a combination thereof.

[0026] The central metal ion can be any one of: alkaline earth metals such as Mg, Ca, or combinations thereof; transition metals such as Zr, Ti, Ni, Mn, Co, V, Nb, Ta, Mo, W, or combinations thereof; transition metals such as Si, Ge, or combinations thereof, metalloids, Al; rare earth metals such as Y, La, or combinations thereof; and combinations thereof.

[0027] The organic ligand may be a carboxylic acid group, a carboxylate anion group, an amino group, an imino group, an amide group, a sulfonic acid group, a sulfonate anion group, a methanedithioic acid group, a methanedithioic acid anion group (-CS 2- ), a compound having one or more functional groups selected from the group consisting of a pyridine group and a pyrazine group, or a mixture thereof.

[0028] The organometallic compound may be a silane coupling agent. This silane coupling agent may be 3-aminopropyltriethoxysilane, 3-(2-aminoethyl)aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-(2-aminoethyl)aminopropylmethyldimethoxysilane, 4-aminobutyltriethoxysilane, or a combination thereof.

[0029] The coating layer may further contain a binder, a conductive material, or a combination thereof. The contents of the binder and the conductive material can be appropriately adjusted and do not need to be limited.

[0030] The negative electrode active material may be a carbon-based negative electrode active material, an Si-based negative electrode active material, or a combination thereof.

[0031] The carbon-based negative electrode active material can include crystalline carbon, amorphous carbon, or a combination thereof. Examples of the crystalline carbon include graphite such as amorphous, plate-shaped, flaky, spherical, or fibrous natural graphite or artificial graphite, and examples of the amorphous carbon include soft carbon or hard carbon, mesophase pitch carbide, calcined coke, and the like.

[0032] The Si-based negative electrode active material is silicon, a silicon-carbon composite, SiO x (0 < x < 2, an Si-Q alloy (wherein Q is selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements (excluding Si), Group 15 elements, Group 16 elements, transition metals, rare earth elements, and combinations thereof), or a combination thereof.

[0033] The silicon-carbon composite may be a composite of silicon and amorphous carbon. According to an embodiment, the silicon-carbon composite may be in the form of silicon particles and the surfaces of the silicon particles coated with amorphous carbon. For example, it may include secondary particles (cores) formed by assembling primary silicon particles and an amorphous carbon coating layer (shell) located on the surfaces of the secondary particles. The amorphous carbon may also be located between the primary silicon particles, for example, the primary silicon particles may be coated with amorphous carbon. The secondary particles may be present dispersed in an amorphous carbon matrix.

[0034] The silicon-carbon composite may further include crystalline carbon. For example, the silicon-carbon composite may include a core including crystalline carbon and silicon particles and an amorphous carbon coating layer located on the core.

[0035] The silicon particles may be silicon nanoparticles.

[0036] The particle size of the silicon nanoparticles may be 10 nm to 1,000 nm, and in another embodiment, 10 nm to 200 nm, or 20 nm to 150 nm. When the particle size of the silicon nanoparticles is within this range, excessive volume expansion that occurs during charging and discharging can be suppressed, and conductive path disconnection due to particle crushing during charging and discharging can be prevented.

[0037] In the negative active material according to one embodiment, the core silicon-carbon composite may include silicon nanoparticles and an amorphous carbon coating layer disposed on the surface of the silicon nanoparticles. The silicon-carbon composite may also include an assembly of at least one silicon nanoparticle and an amorphous carbon coating layer disposed on the surface of the assembly.

[0038] In the amorphous carbon coating layer, the amorphous carbon may be soft carbon or hard carbon, mesophase pitch carbide, calcined coke, or a combination thereof. The thickness of the amorphous carbon coating layer may be 1 nm to 2 μm, 1 nm to 500 nm, 10 nm to 300 nm, or 20 nm to 200 nm. When the thickness of the amorphous carbon coating layer is within the above range, the volume expansion of silicon during charging and discharging can be well suppressed.

[0039] The crystalline carbon may be amorphous, plate-like, flake-like, spherical or fibrous natural graphite, artificial graphite, or a combination thereof.

[0040] When the silicon-carbon composite includes silicon nanoparticles and an amorphous carbon coating layer, the content of the silicon nanoparticles may be 30% to 70% by weight, or 40% to 65% by weight, based on 100% by weight of the entire silicon-carbon composite. Also, the content of the amorphous carbon coating layer may be 30% to 70% by weight, or 35% to 60% by weight, based on 100% by weight of the entire silicon-carbon composite.

[0041] When the silicon-carbon composite further contains crystalline carbon, the content of silicon nanoparticles may be 20% by weight to 70% by weight or 25% by weight to 65% by weight, based on 100% by weight of the entire silicon-carbon composite. The content of amorphous carbon may be 25% by weight to 70% by weight or 25% by weight to 60% by weight, and the content of crystalline carbon may be 1% by weight to 20% by weight or 5% by weight to 15% by weight, based on 100% by weight of the entire silicon-carbon composite.

[0042] In the negative electrode active material layer, the content of the negative electrode active material may be 95% by weight to 98% by weight with respect to 100% by weight of the entire negative electrode active material layer.

[0043] The negative electrode active material layer may include a binder and may further include a conductive material. The content of the binder may be 1 wt% to 5 wt% with respect to 100 wt% of the total negative electrode active material layer. The content of the conductive material may be 1 wt% to 5 wt% with respect to 100 wt% of the total negative electrode active material layer.

[0044] The binder serves to adhere the negative active material particles to each other and to the current collector well. The binder may be a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof.

[0045] Examples of the non-aqueous binder include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or a combination thereof.

[0046] The aqueous binder may be selected from styrene-butadiene rubber, (meth)acrylate styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinylpyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, and combinations thereof.

[0047] The negative electrode binder may be a cellulose-based compound, and the cellulose-based compound may be used in combination with the aqueous binder. The cellulose-based compound may be a mixture of one or more of carboxymethylcellulose, hydroxypropylmethylcellulose, methylcellulose, or alkali metal salts thereof. The alkali metal may be Na, K, or Li. The cellulose-based compound may function as a binder, or as a thickener that can impart viscosity. The cellulose-based compound may be used at an appropriate content within the binder content, and may be, for example, 0.1 to 3 parts by weight per 100 parts by weight of the negative electrode active material.

[0048] The dry binder is a polymeric material that can be fiberized, and may be, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or a combination thereof.

[0049] The conductive material is used to impart conductivity to the electrodes, and any material that does not cause chemical changes in the battery and is electronically conductive can be used. Specific examples include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, carbon nanofiber, and carbon nanotube; metal-based materials in the form of metal powder or metal fiber, including copper, nickel, aluminum, and silver; conductive polymers such as polyphenylene derivatives; and mixtures thereof.

[0050] The current collector may be selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof.

[0051] <Method of manufacturing the negative electrode> The negative electrode according to an embodiment can be manufactured by the following process.

[0052] A coating layer composition including an organometallic material and a solvent is pattern-coated on a current collector and dried to form a coating layer. The solvent may be water, an organic solvent, or a combination thereof. The organic solvent may be an alcohol such as methanol, ethanol, propanol, or isopropanol.

[0053] The pattern coating can be performed by gravure coating, 2-roll reverse coating, screen coating, slot die coating, or 2-roll coating, but may be performed by any coating process commonly used in the art, provided that the pattern can be formed.

[0054] Then, a negative electrode active material layer composition is applied to the coating layer and dried to form a negative electrode active material layer, followed by a rolling process to manufacture a negative electrode.

[0055] The negative electrode active material layer composition includes a negative electrode active material, a binder, and optionally a conductive material, and also includes a solvent, which may be an organic solvent such as N-methylpyrrolidone or water.

[0056] <Lithium secondary battery> Another embodiment provides a lithium secondary battery including a negative electrode, a positive electrode, and an electrolyte.

[0057] The negative electrode may be an negative electrode according to an embodiment.

[0058] [Positive electrode] The positive electrode may include a current collector and a positive electrode active material layer formed on the current collector.

[0059] The positive electrode active material layer may further include a binder and / or a conductive material, and may further include an additive capable of acting as a sacrificial positive electrode.

[0060] The positive electrode active material may be a compound capable of reversibly inserting and extracting lithium (lithiate intercalation compound). Specifically, one or more of composite oxides of lithium and a metal selected from cobalt, manganese, nickel, and combinations thereof may be used.

[0061] The composite oxide may be a lithium transition metal composite oxide, and specific examples thereof include lithium nickel-based oxides, lithium cobalt-based oxides, lithium manganese-based oxides, lithium iron phosphate-based compounds, cobalt-prenix-manganese-based oxides, or combinations thereof.

[0062] As an example, a compound represented by any one of the following chemical formulas can be used: a A 1-b X b O 2-c D c (0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05;Li a Mn 2-b X b O 4-c D c (0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05;Li a Ni 1-b-c Co b X c O 2-α D α (0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.5, 0<α<2;Li a Ni 1-b-c Mn b X c O 2-α D α (0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.5, 0<α<2;Li a Ni b Coc L 1 d GeO2(0.90≦a≦1.8, 0≦b≦0.9, 0≦c≦0.5, 0≦d≦0.5, 0≦e≦0.1;Li a NiG b O2(0.90≦a≦1.8, 0.001≦b≦0.1;Li a CoG b O2(0.90≦a≦1.8, 0.001≦b≦0.1;Li a Mn 1-b G b O2(0.90≦a≦1.8, 0.001b≦0.1;Li a Mn2G b O4(0.90≦a≦1.8, 0.001≦b≦0.1;Li a Mn 1-g G g PO4(0.90≦a≦1.8, 0≦g≦0.5;Li 3-f )Fe2(PO4)3(0≦f≦2;Li a FePO4(0.90≦a≦1.8).

[0063] In the above formula, A is Ni, Co, Mn, or a combination thereof; X is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element, or a combination thereof; D is O, F, S, P, or a combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V, or a combination thereof; L 1 is Mn, Al or a combination thereof.

[0064] As an example, the positive electrode active material may be a high-nickel positive electrode active material in which the nickel content is 80 mol% or more, 85 mol% or more, 90 mol% or more, 91 mol% or more, or 94 mol% or more and 99 mol% or less relative to 100 mol% of metals excluding lithium from the lithium transition metal composite oxide. The high-nickel positive electrode active material can achieve high capacity and can be applied to high-capacity, high-density lithium secondary batteries.

[0065] In the positive electrode, the content of the positive electrode active material may be 90% by weight to 98% by weight based on the total weight of the positive electrode active material layer, and the contents of the binder and the conductive material may be 1% by weight to 5% by weight, respectively, based on the total weight of the positive electrode active material layer.

[0066] The binder serves to adhere the positive electrode active material particles to each other and to adhere the positive electrode active material to the current collector. Representative examples of the binder include, but are not limited to, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylate styrene-butadiene rubber, epoxy resin, (meth)acrylic resin, polyester resin, and nylon.

[0067] The conductive material is used to impart electrical conductivity to the electrodes, and any material that does not undergo chemical change in the battery and is electronically conductive can be used. Examples of the conductive material include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, carbon nanofiber, and carbon nanotube; metal-based materials in the form of metal powder or metal fiber containing copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; and mixtures thereof.

[0068] The current collector may be made of Al, but is not limited to this.

[0069] [Electrolyte] The electrolyte includes a non-aqueous organic solvent and a lithium salt.

[0070] The non-aqueous organic solvent serves as a medium through which ions involved in the electrochemical reaction of the battery can move.

[0071] The non-aqueous organic solvent may be a carbonate-based, ester-based, ether-based, ketone-based, alcohol-based, or aprotic solvent.

[0072] The carbonate-based solvents include Dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. can be used. As the ester-based solvent, methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanolide, mevalonolactone, valerolactone, caprolactone, etc. can be used. As the ether-based solvent, dibutyl ether, tetraglyme, diglyme, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, etc. can be used. As the ketone-based solvent, cyclohexanone, etc. can be used. Examples of the alcohol solvent include ethyl alcohol and isopropyl alcohol, and examples of the aprotic solvent include nitriles such as R-CN (R is a hydrocarbon group having a linear, branched, or cyclic structure having 2 to 20 carbon atoms and may contain a double bond, an aromatic ring, or an ether group); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane and 1,4-dioxolane; and sulfolanes.

[0073] The non-aqueous organic solvents can be used alone or in combination of two or more kinds.

[0074] When a carbonate-based solvent is used, a cyclic carbonate and a chain carbonate can be mixed and used, and the cyclic carbonate and the chain carbonate can be mixed in a volume ratio of 1:1 to 1:9.

[0075] The lithium salt is a substance that dissolves in an organic solvent, acts as a source of lithium ions in a battery, enables the operation of a basic lithium secondary battery, and plays a role in promoting the movement of lithium ions between the positive electrode and the negative electrode. Representative examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide (LiFSI), LiC4F9SO3, LiN(C x F2 x+1 SO2)(C y F 2y+1 SO2) (x and y are integers from 1 to 20), lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalato)phosphate (LiDFOB), and lithium bis(oxalato)borate (LiBOB).

[0076] [Separator] Depending on the type of lithium secondary battery, a separator may be present between the positive and negative electrodes. As such a separator, polyethylene, polypropylene, polyvinylidene fluoride, or a multilayer film of two or more layers of these may be used, and it is of course possible to use a mixed multilayer film such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, or a polypropylene / polyethylene / polypropylene three-layer separator.

[0077] The separator may include a porous substrate and a coating layer comprising an organic material, an inorganic material, or a combination thereof located on one or both sides of the porous substrate.

[0078] The porous substrate may be a polymer membrane formed of any one polymer selected from polyolefins such as polyethylene and polypropylene, polyesters such as polyethylene terephthalate and polybutylene terephthalate, polyacetal, polyamide, polyimide, polycarbonate, polyether ketone, polyaryl ether ketone, polyetherimide, polyamide imide, polybenzimidazole, polyether sulfone, polyphenylene oxide, cycloolefin copolymers, polyphenylene sulfide, polyethylene naphthalate, glass fiber, Teflon, and polytetrafluoroethylene, or a copolymer or mixture of two or more of these polymers.

[0079] The organic material may include a polyvinylidene fluoride polymer or a (meth)acrylic polymer.

[0080] The inorganic material may include, but is not limited to, inorganic particles selected from Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, and combinations thereof.

[0081] The organic material and the inorganic material may be mixed in one coating layer, or may be stacked in a coating layer including an organic material and a coating layer including an inorganic material.

[0082] Lithium secondary batteries can be classified into cylindrical, square, pouch, coin, and other types according to their shapes. FIGS. 2 to 5 are schematic diagrams showing a lithium secondary battery according to an embodiment, in which FIG. 2 shows a circular battery, FIG. 3 shows a square battery, and FIGS. 4 and 5 show a pouch battery. Referring to FIGS. 2 to 5, the lithium secondary battery 100 can include an electrode assembly 40 having a separator 30 interposed between a positive electrode 10 and a negative electrode 20, and a case 50 in which the electrode assembly 40 is housed. The positive electrode 10, the negative electrode 20, and the separator 30 can be impregnated with an electrolyte (not shown). The lithium secondary battery 100 can include a sealing member 60 that seals the case 50 as shown in FIG. 2. Also, in FIG. 3, the lithium secondary battery 100 can include a positive electrode lead tab 11, a positive electrode terminal 12, a negative electrode lead tab 21, and a negative electrode terminal 22. As shown in FIGS. 4 and 5, the lithium secondary battery 100 may include electrode tabs 70, i.e., a positive electrode tab 71 and a negative electrode tab 72, which serve as electrical paths for conducting the current generated in the electrode assembly 40 to the outside.

[0083] The lithium secondary battery according to an embodiment of the present invention may be applied to automobiles, mobile phones, and / or various types of electric devices, but the present invention is not limited thereto.

[0084] Examples of the present invention and comparative examples are described below. The following examples are merely examples of the present invention, and the present invention is not limited to the following examples.

[0085] Example 1 A coating layer slurry was prepared by adding 3-aminopropyltriethoxysilane coupling agent to ethanol.

[0086] A negative electrode active material layer slurry was prepared by mixing 97.5 wt % of a silicon-carbon composite negative electrode active material, 1.5 wt % of carboxymethyl cellulose, and 1 wt % of styrene-butadiene rubber in an aqueous solvent.

[0087] The silicon-carbon composite includes an assembly of secondary particles assembled with silicon nanoparticles having an average particle size of 100 nm, and a soft carbon coating layer formed on the surface of the assembly, in which the silicon nanoparticles were 60 wt % and the soft carbon amorphous carbon was 40 wt % relative to 100 wt % of the entire silicon-carbon composite, and the thickness of the soft carbon coating layer was 100 nm.

[0088] The coating layer slurry was gravure pattern coated on a copper foil current collector to form a coating layer having a pattern shape with an area of ​​20% of the total area of ​​the negative electrode active material layer (100%). The negative electrode active material layer slurry was then coated on the resulting product, dried, and rolled to produce a negative electrode having a current collector, a coating layer, and a negative electrode active material layer.

[0089] The width of the pattern was 5 μm, and the interval between adjacent patterns was 20 μm.

[0090] A half-cell was fabricated in a conventional manner using the negative electrode, lithium metal counter electrode, and electrolyte, which was a mixture of 1M LiPF6 dissolved in ethylene carbonate and dimethyl carbonate (volume ratio 3:7).

[0091] (Examples 2 to 4) A negative electrode and a half cell were manufactured in the same manner as in Example 1, except that the area percentage of the coating layer, the width of the pattern, and the interval between adjacent patterns were changed as shown in Table 1 below.

[0092] Comparative Example 1 A negative electrode active material layer slurry was prepared by mixing 97.5 wt % of a silicon-carbon composite negative electrode active material, 1.5 wt % of carboxymethyl cellulose, and 1 wt % of styrene-butadiene rubber in an aqueous solvent.

[0093] The silicon-carbon composite includes an assembly of secondary particles assembled with silicon nanoparticles having an average particle size of 100 nm, and a soft carbon coating layer formed on the surface of the assembly, in which the silicon nanoparticles were 60 wt % and the soft carbon amorphous carbon was 40 wt % relative to 100 wt % of the entire silicon-carbon composite, and the thickness of the soft carbon coating layer was 100 nm.

[0094] The negative electrode active material layer was coated on a copper foil current collector, dried, and then rolled to prepare a negative electrode having a current collector and a negative electrode active material layer.

[0095] A half cell was manufactured in the same manner as in Example 1 using the negative electrode.

[0096] Comparative Example 2 A coating layer was formed by coating the entire surface of a copper foil current collector with the coating layer slurry of Example 1 and drying the coating layer, that is, the area percentage of the coating layer was 100% with respect to the total area of ​​the negative active material layer, which was 100%.

[0097] Then, the negative electrode active material layer slurry of Example 1 was coated on the coating layer, followed by drying and rolling to prepare a negative electrode having a current collector, a coating layer and a negative electrode active material layer.

[0098] Comparative Example 3 A negative electrode and a half cell were manufactured in the same manner as in Example 1, except that the coating layer slurry was prepared using styrene-butadiene rubber instead of 3-aminopropyltriethoxysilane coupling agent.

[0099] (Comparative Examples 4 and 5) A negative electrode and a half cell were manufactured in the same manner as in Example 1, except that the area percentage of the coating layer, the width of the pattern, and the interval between adjacent patterns were changed as shown in Table 1 below.

[0100] Experimental example 1) Adhesion strength evaluation In Examples 1 to 4 and Comparative Examples 1 to 5, the adhesive strength between the current collector and the negative active material layer was measured using a tensile tester (Shimadzu Corporation) at 90° fill test at 100 mm / min. The results are shown in Table 1 below.

[0101] Experimental example 2) Evaluation of negative electrode non-resistance The resistance of the negative electrodes prepared in Examples 1 to 4 and Comparative Examples 1 to 5 was measured using a resistance meter made by HIOKI (resistance value passing vertically through the negative electrode, through plane), and the results are shown in Table 1 below.

[0102] [Table 1]

[0103] As shown in Table 1 above, the negative electrodes of Examples 1 to 4 exhibited excellent adhesion and low resistance.

[0104] On the other hand, Comparative Example 1, which did not have a coating layer, showed too low adhesive strength, and Comparative Example 2, in which the coating layer was formed over 100% of the negative electrode active material layer area, showed too high adhesive strength and resistivity to be measured.

[0105] Furthermore, it was found that Comparative Example 4, in which the area percentage of the coating layer was too low, had too low adhesive strength, and Comparative Example 5, in which the area percentage of the coating layer was too high, had too high non-resistance.

[0106] Although the preferred embodiment of the present invention has been described above, the present invention is not limited thereto, and various modifications can be made within the scope of the claims, the summary of the invention, and the accompanying drawings, and it is natural that these also fall within the scope of the present invention.

Claims

1. Current collector; A negative electrode active material layer including a negative electrode active material; and The negative electrode for a lithium secondary battery further comprises a coating layer disposed between the current collector and the negative electrode active material layer, the coating layer including an organometallic material and having a pattern shape.

2. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the organometallic material is an organometallic compound in which a central metal ion is coordinately bonded to an organic ligand, or a combination thereof.

3. 3. The negative electrode for a lithium secondary battery according to claim 2, wherein the central metal ion is any one of: an alkaline earth metal, which is Mg, Ca, or a combination thereof; a transition metal, which is Zr, Ti, Ni, Mn, Co, V, Nb, Ta, Mo, W, or a combination thereof; a semimetal, which is Si, Ge, or a combination thereof, a transition metal, which is Al; a rare earth metal, which is Y, La, or a combination thereof; and combinations thereof.

4. 3. The negative electrode for a lithium secondary battery according to claim 2, wherein the organic ligand is a compound having one or more functional groups selected from the group consisting of a carboxylic acid group, a carboxylate anion group, an amino group, an imino group, an amide group, a sulfonic acid group, a sulfonate anion group, a methanedithioic acid group, a methanedithioic acid anion group, a pyridine group, and a pyrazine group, or a mixture thereof.

5. 3. The negative electrode for a lithium secondary battery according to claim 2, wherein the organometallic compound is a silane coupling agent.

6. The silane coupling agent is 3-aminopropyltriethoxysilane, 3-(2-aminoethyl)aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-(2-aminoethyl)aminopropylmethyldimethoxysilane, 4-aminobutyltriethoxysilane, or a combination thereof. The negative electrode for lithium secondary batteries according to claim 5.

7. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein an area of ​​the coating layer is 10% to 50% of a total area of ​​the negative electrode active material layer.

8. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the spacing between adjacent patterns is 20 μm or more.

9. 9. The negative electrode for a lithium secondary battery according to claim 8, wherein the spacing between adjacent patterns is 20 μm to 100 μm.

10. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the width of the pattern is 5 μm to 30 μm.

11. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the pattern shape is a mesh shape, a dot shape, a diagonal line shape, an ellipse shape, a polygonal shape, a rhombus shape, a line shape, a wave shape, a triangular pyramid shape, or a combination thereof.

12. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the negative electrode active material is a carbon-based negative electrode active material, a Si-based negative electrode active material, or a combination thereof.

13. The negative electrode for a lithium secondary battery according to claim 12 , wherein the carbon-based negative electrode active material is crystalline carbon, amorphous carbon, or a combination thereof.

14. The Si-based negative electrode active material is silicon, a silicon-carbon composite, SiO x (0<x<2), a Si-Q alloy (wherein Q is selected from an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element (excluding Si), a Group 15 element, a Group 16 element, a transition metal, a rare earth element, and a combination thereof), or a combination thereof.

15. The negative electrode for a lithium secondary battery according to claim 1 , wherein the negative electrode active material layer further comprises a binder.

16. The negative electrode for a lithium secondary battery according to claim 1 , wherein the negative electrode active material layer further contains a conductive material.

17. The negative electrode for a lithium secondary battery according to any one of claims 1 to 16; a positive electrode; and A lithium secondary battery comprising an electrolyte.

Citation Information

Patent Citations

  • Electrode for battery and its manufacture

    JP1999073947A

  • Negative electrode for lithium secondary battery and battery using it

    JP2006260784A

  • Negative-electrode mixture for non-aqueous electrolyte secondary cell, negative electrode for non-aqueous electrolyte secondary cell containing said mixture, non-aqueous electrolyte secondary cell provided with said negative electrode, and electrical device

    WO2014207967A1